2014
DOI: 10.1039/c4tc01385a
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies on magnetism and the optical properties of transition metal embedded graphitic carbon nitride sheets

Abstract: Transition metal embedded g-C3N4 sheets demonstrate promising multi usage in various fields such as memory devices, photocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(83 citation statements)
references
References 79 publications
4
77
2
Order By: Relevance
“…This is confirmed well by Fig. [28,46,47] Consulting the results in V-, Cr-, and Fe-g-C 3 N 4 , we could preliminarily conclude that the B-doped g-C 3 N 4 system possess ferromagnetism at room temperature. We found that the B-doing could greatly increase the electrical conductivity because of the formation of delocalized π-bonds.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…This is confirmed well by Fig. [28,46,47] Consulting the results in V-, Cr-, and Fe-g-C 3 N 4 , we could preliminarily conclude that the B-doped g-C 3 N 4 system possess ferromagnetism at room temperature. We found that the B-doing could greatly increase the electrical conductivity because of the formation of delocalized π-bonds.…”
Section: Resultssupporting
confidence: 83%
“…anti-π orbital (π*), and therefore the magnetic moments arise mainly from the p z orbitals, making it n-doped in nature. Therefore, the 3d-orbitals are fully filled with a Cu +1 valence state for Cu-dope gt-C 3 N 4 , and hence contain a minute amount of unpaired electron [28] , resulting in a slight magnetic moment on Cu site. [24,26] Figure 3 shows the charge transport is dominated by the spin-down electron for B-doped case, but by the spin-up electron for Al-and Cu-doped cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations